1994
DOI: 10.1093/ajcp/102.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Breast Fine-needle Aspiration:A Comparison of Thin-layer and Conventional Preparation

Abstract: Two hundred forty-two breast fine-needle aspirates prepared by the Cytyc ThinPrep Processor were compared with aspirates prepared by the conventional smear method. Palpable and nonpalpable mammographic breast lesions were aspirated and the first half of the aspirate was submitted for conventional smears and the second half was rinsed into a proprietary fixative and loaded on the ThinPrep Processor for monolayer slide preparation. The matched pairs were diagnosed and analyzed separately in a double-blinded mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 12 publications
7
73
2
Order By: Relevance
“…4,6,17,18 On the other hand, alterations in architecture and cellular morphology as well as loss of informative background are usually seen in FNA smears prepared by LBC. 16,17,19,20,21 In the present study, the age range and mean age was comparable with other studies. 4,16,19 In our study 53% of tumours were located in the right breast whereas 47% of tumours were located in the left breast which was similar to the findings of Ryu HS et al 16 In the present study we compared 100 MLBC and conventional FNA smears on following Cytomorphological parameters:-…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…4,6,17,18 On the other hand, alterations in architecture and cellular morphology as well as loss of informative background are usually seen in FNA smears prepared by LBC. 16,17,19,20,21 In the present study, the age range and mean age was comparable with other studies. 4,16,19 In our study 53% of tumours were located in the right breast whereas 47% of tumours were located in the left breast which was similar to the findings of Ryu HS et al 16 In the present study we compared 100 MLBC and conventional FNA smears on following Cytomorphological parameters:-…”
Section: Discussionsupporting
confidence: 90%
“…Perez-Reyes et al 19 employed split sampling technique where they divided the aspirate into two halves, one for LBC and the other for CS, hence in their study the cellularity of LBC was inferior to CS. Gerhard R et al 22 observed that the number of passes performed and the skills of the person performing the procedure determine the quality and cellularity of the samples.…”
Section: Cellularitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Leung et al 5 and Perez-Reyes et al 7 , we discovered the cytoplasmic characteristics to be comparable in both the CS and thin-layer methods of preparation; however, we found notable qualitative differences in the nuclei of both ductal and myoepithelial cells in our study. Ductal and myoepithelial cell nuclei tended to have visible small nucleoli, and the chromatin pattern was more enhanced in MP slides compared with CS slides.…”
Section: Discussionsupporting
confidence: 90%
“…[5][6][7] We were very careful to obtain equivalent cellular material for both methods, and yet we noticed that in many cases there seemed to be only enough fluid to make one slide, with only a small residual amount of fluid left in the vial. We therefore suspect that significant cellular loss probably occurred during one or more of the several MP processing steps.…”
Section: Discussionmentioning
confidence: 99%